Kebijakan Dynamic Defence Force Jepang dalam Merespon Pengembangan Senjata Nuklir Korea Utara (2010-2016) - Paliama, Jeremia Kevin; Priadarsini, Ni Wayan Rainy; Suwecawangsa, Adi P. (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2018), 2018)
ABSTRACT   North Korea frequently conduct tests of nuclear weapons has made Japan a worried over these actions. Although North Korea does not directly target the missile to the Japan territorial, still Japan government criticized sharply over the nuclear weapons test. North Korea’s nuclear weapons that can directly reach Japan frequently surely make Japan feel threatened. Japan decided to change the military concept from Basic Defence Force t into a Dynamic Defence Force. The base Defence Force Basic defense Concept focused on building strong-power passive defense. As the research question is how Japan through Dynamic Defence Force policy to respond to North Korea's nuclear weapons development, this research aims to analyze how Dynamic Defence Force policy of Japan being able to respond and mitigate the threat posed through the ownership of its nuclear weapons by using the concept of the balance of threat and deterrence.The concept analyzes how a country is doing a balancing act as a deterrence effort to be able to protect against the threats that exist. For that Japan decided to change the concept of the defence of the Basic Defence Force into a Dynamic Defence Force, because Japan felt that the concept of the Basic Defence Force are no longer able to protect his country from the threats that exist.This research uses qualitative descriptivemethod with the use of the official documents issued by Japan and the related journals as a source of data.   Keywords : Japan, North Korea, The Basic Defence Force, The Basic Dynamic Defence Force, Nuclear Weapons